Gramsci, Clausewitz, guerra e política - Passos, Rodrigo Duarte Fernandes dos [UNESP] (My University, 2014)
The aim of this text is to draft an answer to the following questions: What is the relationship between war and politics in Antonio Gramsci’s thought? How is it possible to make a relationship of war and politics according to Gramsci with Prussian general Carl von Clausewitz’s same themes? The main hypothesis of this article points to understand that war as a metaphor of politics approach – predominant point in Gramsci’s approach of war – has a broader meaning that war as an interstate conflict, which is Clausewitz’s concept. Although the war is connected with politics in both authors, interstate conflict has a stronger emphasis in clausewitzian sense and a wider sense of war as politics is found in gramscian approach.

O objetivo do texto é esboçar uma resposta às seguintes questões: Qual a relação entre guerra e política no pensamento de Antonio Gramsci? Como relacionar guerra e política em Gramsci às teses sobre tais temas do general prussiano Carl Von Clausewitz? A hipótese central que orienta o raciocínio do artigo sustenta que a abordagem da guerra como metáfora da política - ponto predominante na abordagem da guerra no pensamento de Gramsci - tem sentido muito mais amplo do que a guerra no sentido de um conflito interestatal, conceito trabalhado por Clausewitz. Em que pese a conexão da guerra com a política em ambos os autores, o conflito interestatal se coloca predominantemente no sentido clausewitziano e o sentido mais amplo de guerra como política na abordagem gramsciana.
Keywords: Gramsci; Clausewitz; guerra; política